Quality assessment of yak oocytes for in vitro production of yak embryos - HUSSAIN, M; CHAKRAVARTY, P; CHAUHAN, M S; SOREN, S; BORAH, B K D; DOLEY, J; DAS, P J (The Indian Journal of Animal Sciences, 2014)
Yak oocytes were isolated and morphologically classified into 3 categories, i.e. good, fair and poor quality oocytes according to the compactness of the cumulus cells, and were assigned for in vitro maturation, fertilization and embryonic development. Oocytes were retrieved by both aspiration and post-aspiration slicing technique, and the overall recovery rates of good, fair and poor quality oocytes were estimated at 46.55, 30.6 and 22.84% respectively. Maturation rates (M II) in good quality oocytes were significantly higher as compared to that in fair and poor quality oocytes. Total and normal fertilization rates were also higher in good quality oocytes than in fair and poor oocytes. Good quality oocytes led to embryonic development with significant numbers of transferrable embryos (i.e. morula and blastocyst); 60% of morula was further developed to blastocyst. Thus, it is concluded that the selection of good oocytes according to cumulus cells compactness is an important criterion for in vitro maturation, fertilization, and embryonic development in yaks.